2010
DOI: 10.13181/mji.v19i2.389
|View full text |Cite
|
Sign up to set email alerts
|

The nerve protection and in vivo therapeutic effect of <em>Acalypha indica</em> extract in frogs

Abstract: Tujuan Membuktikan efek neuroproteksi dan/atau neuroterapi ekstrak air Acalypha indica Linn. pada katak yang dilumpuhkan dengan injeksi pankuronium bromida Metode Enam puluh ekor katak (Bufo melanostictus Schneider) dibagi ke dalam dua kelompok perlakuan yaitu kelompok neuroproteksi dan neuroterapi. Setiap kelompok dibagi ke dalam 6 subkelompok yaitu kontrol negatif (diberi air); kontrol positif (pirasetam), dan 4 kelompok dosis ekstrak: 200, 300, 400, 500 mg/KgBB. Pankuronim bromida 0,2 %, pelumpuh otot, disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The result of this examination showed that Acalypha indica Linn root extract has an effect on increasing the number of viable post-hypoxic nerve cells. The result was consistent with research by Purwaningsih et al 14 in which the optimal neurotherapy dose was seen at dose 20 mg/mL. The dose-dependent increase in relative cell viability raises the possibility that a higher dose than 20 mg/mL would further enhance the cell viability, thus further research to assess the effect of Acalypha indica Linn root extract on relative cell viability of hippocampal tissue posthypoxia with higher doses needs to be performed to obtain the optimal dose for the increase of post-hypoxic relative cell viability.…”
Section: Discussionsupporting
confidence: 94%
“…The result of this examination showed that Acalypha indica Linn root extract has an effect on increasing the number of viable post-hypoxic nerve cells. The result was consistent with research by Purwaningsih et al 14 in which the optimal neurotherapy dose was seen at dose 20 mg/mL. The dose-dependent increase in relative cell viability raises the possibility that a higher dose than 20 mg/mL would further enhance the cell viability, thus further research to assess the effect of Acalypha indica Linn root extract on relative cell viability of hippocampal tissue posthypoxia with higher doses needs to be performed to obtain the optimal dose for the increase of post-hypoxic relative cell viability.…”
Section: Discussionsupporting
confidence: 94%
“…22 Medicinal plants have been known that contain several compounds besides polyphenol and flavonoids that support each other to provide a beneficial effect. 17 The root extract of AI has been used in several studies [6][7][8]11 and its compounds have been proven Vol. 27, No.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the root extract of Acalypha indica L. (AI) exhibited neuroprotective and neurotherapeutic effects on the neuromuscular junction and was able to inhibit the activity of neurotoxin on isolated frog tissues ex vivo 6 and in vivo. 7 The extract was also found to be effective in improving the rat hippocampal nerve cells at doses of 400 and 500 mg/kg BB. 8 On the other hand, Centella asiatica L. (CA) extract has been reported to be a peripheral vasodilator in neurological disorders and also improves circulation.…”
mentioning
confidence: 94%
“…In the previous study, the water extract of the roots of AI for animal models proved to have a neuroprotective effect [26]. For his studies, mechanisms of plant AI as therapies on MG were done by assessing the autonomic condition on heart muscle will be tested.…”
Section: Krisnamurti Et Almentioning
confidence: 99%